Partnering with patients in clinical trials of pain treatments: a narrative review. Issue 10 (28th October 2022) - Holzer, Katherine J.; Veasley, Christin; Kerns, Robert D.; Edwards, Robert R.; Gewandter, Jennifer S.; Langford, Dale J.; Yaeger, Lauren H.; McNicol, Ewan; Ferguson, McKenzie; Turk, Dennis C.; Dworkin, Robert H.; Haroutounian, Simon
Abstract: The interest and the rationale for meaningful engagement of patients as partners in clinical trials of pain treatments has been increasing. No specific guidance on patient engagement for pain research studies currently exists; thus, the goal of this narrative review was to provide a historical perspective and a current evaluation of the literature on engaging patients as partners in clinical studies in general and in pain-related studies more specifically. We described how regulatory and funding agencies have developed approaches to incorporate input from patients and patient partners in their decision-making processes. We provided an overview on key practices of patient recruitment and engagement as partners in clinical research and highlighted the perceived benefits and challenges of such partnerships. We summarized factors that can facilitate or hinder meaningful patient engagement in clinical trials of pain treatments and outlined gaps that future research should address to optimize patient-centered clinical research.